Localization of components of the renin-angiotensin system in the suprachiasmatic nucleus of normotensive Sprague-Dawley rats: part B. Angiotensin II (AT1)-receptors, a light and electron microscopic study - Thomas, Martin Alexander; Fleissner, Gerta; Stöhr, Marion; Hauptfleisch, Stefan; Lemmer, Björn (Brain research, 2004)
The dominant pacemaker of the mammalian circadian clock, located in the suprachiasmatic nucleus (SCN), is of special interest for many pharmacological, physiological and immunohistological studies on angiotensins and their receptors. Based on its role in the circadian modulation of blood pressure and vasopressin release, the distribution and function of the neuropeptide angiotensin II (ANG II) and its AT1-receptors (AT1) in the SCN became a target for several immunohistological studies. Though the distribution of ANG II and vasopressin in the SCN is well known at light microscopic level, detailed data concerning the AT1-receptor distribution in the SCN is missing. To confirm the mechanisms by which ANG II exerts its actions in the SCN, it is vital to understand how the brain renin-angiotensin system is organized at the cellular level, including the distribution of ANG II and the ANG II (AT1)-receptors as well as the protein-receptor complex. The current paper presents a light- and electron microscopic study on AT1-receptor-immunolabeling in the suprachiasmatic nucleus of normotensive Sprague-Dawley rats.
Gesehen am 17.03.2022